The Balder effect: conditional arbitrability's threat to the New York convention. (10th January 2023) - Lewis, Alfred
Abstract: This article assesses the Russian rules for the arbitrability of certain types of Russian corporate and procurement disputes, under which the arbitration must be seated in Russia. It is argued that these rules violate the New York Convention, and that other States Party to the Convention should object to the Russian rules. Finally the article suggests that an available and effective means of so objecting can be found in the principle of reciprocity under the Convention.